2014
DOI: 10.1186/1472-6785-14-17
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between seasonality and density: consequences for female breeding decisions in a small cyclic herbivore

Abstract: BackgroundCyclic rodent population dynamics are subjected to both intrinsic regulatory processes such as density-dependence and extrinsic environmental forcing. Among extrinsic factors, seasonal environmental variation is understood to facilitate cycles. In rodents, these processes have been studied mostly independently and their relative importance for population dynamics is poorly known.ResultsWe performed a detailed analysis of common vole (Microtus arvalis) reproduction in a cyclic population using a spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Several assumptions related to this hypothesis have never been tested. In particular, only a handful of studies have linked increased availability of presumed high‐quality food items to actual ingestion of those foods (Janova, Heroldova & Cepelka, 2016) and consequently increased reproduction rates (but see Sullivan & Sullivan, 2014; Pinot, Gauffre & Bretagnolle, 2014). While there is no question that food quality does affect a range of aspects of herbivore health (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several assumptions related to this hypothesis have never been tested. In particular, only a handful of studies have linked increased availability of presumed high‐quality food items to actual ingestion of those foods (Janova, Heroldova & Cepelka, 2016) and consequently increased reproduction rates (but see Sullivan & Sullivan, 2014; Pinot, Gauffre & Bretagnolle, 2014). While there is no question that food quality does affect a range of aspects of herbivore health (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In common voles and meadow voles, it has been shown that density has a direct impact on reproduction [17,18]. Indeed, during phases of high density, reproduction decreases in these voles leading to stabilization of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Population cycle is commonly observed in the regions with the stable climate and overpopulation is assumed as a limiting factor for a population growth. In this case, peak abundance is accompanied by low breeding success [5][6][7][8]. Developmental stability, which can be estimated by fluctuating asymmetry of morphological characters, is another population parameter.…”
Section: Introductionmentioning
confidence: 99%